Recognition by the Court of The Legal Effect of a Written Contract On the Transfer of Real Estate - Sztermen, Orsolya Lili (Central European Academy Law Review, 2025)
The scope of this article is to consider the validity requirements of effective ownership transfer of real estate through contracts in Hungary. The transfer of movable and immovable property ownership has diverse requirements to be valid in terms of a contract. This article thus determines what regulations and formal criteria need to be met by a seller and a buyer in acquiring the ownership of immovable properties, that is, what makes a contract valid and effective and capable of raising legal consequences and having a binding force. While invalid contracts can also be formulated to be valid and effective in special cases, invalidity rules are diverse, depending on what type of ownership transfer established by the sale contract.